2017
DOI: 10.1186/s13014-017-0919-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the prescription isodose line for Gamma Knife radiosurgery using the shot within shot technique

Abstract: Background: This work explores how the choice of prescription isodose line (IDL) affects the dose gradient, target coverage, and treatment time for Gamma Knife radiosurgery when a smaller shot is encompassed within a larger shot at the same stereotactic coordinates (shot within shot technique). Methods: Beam profiles for the 4, 8, and 16 mm collimator settings were extracted from the treatment planning system and characterized using Gaussian fits. The characterized data were used to create over 10,000 shot wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…3 Although multiple phase III trials have evaluated SRS in the treatment of 1 to 4 brain metastases, [4][5][6][7] there are limited data regarding the role of SRS for a larger number of metastases, 8 in part because of the prohibitively long treatment times associated with an increasing number of lesions, each requiring additional shots or separate isocenters for gamma knifeebased radiosurgery or linearaccelerator based radiosurgery, respectively. 9,10 Volumetric modulated arc therapy (VMAT) is a novel, intensity modulated radiation therapyebased plan optimization platform that permits treatment of multiple lesions using a single isocenter through modulation of gantry rotation, collimation, and dose rate. 11 Although several studies have reported the dosimetric feasibility of this technique, [12][13][14] there are little clinical data to support its safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…3 Although multiple phase III trials have evaluated SRS in the treatment of 1 to 4 brain metastases, [4][5][6][7] there are limited data regarding the role of SRS for a larger number of metastases, 8 in part because of the prohibitively long treatment times associated with an increasing number of lesions, each requiring additional shots or separate isocenters for gamma knifeebased radiosurgery or linearaccelerator based radiosurgery, respectively. 9,10 Volumetric modulated arc therapy (VMAT) is a novel, intensity modulated radiation therapyebased plan optimization platform that permits treatment of multiple lesions using a single isocenter through modulation of gantry rotation, collimation, and dose rate. 11 Although several studies have reported the dosimetric feasibility of this technique, [12][13][14] there are little clinical data to support its safety and efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that this methodoly is acceptable considering that standard GKP radiosurgery are commonly prescribed in 50% IDL [14].…”
Section: Selectivity (S)mentioning
confidence: 99%
“…From Figure 5, we could observe that the gradient of the profile was highly depending on the selected IDL. Johnson et al reported for a single shot setting; the dose gradient in axial plane was the steepest at 56%–63%, 62%–70%, and 77%–84% IDL for 4‐, 8‐, and 16‐mm cones, respectively, based on their shot within shot technique 15 . Unlike other planning systems, shells currently are not allowed in this version of GammaPlan, and only GI (the dose falloff at 50% of the prescription) was incorporated in the optimization, which was distal to the target location.…”
Section: Discussionmentioning
confidence: 99%
“…Johnson et al reported for a single shot setting; the dose gradient in axial plane was the steepest at 56%–63%, 62%–70%, and 77%–84% IDL for 4‐, 8‐, and 16‐mm cones, respectively, based on their shot within shot technique. 15 Unlike other planning systems, shells currently are not allowed in this version of GammaPlan, and only GI (the dose falloff at 50% of the prescription) was incorporated in the optimization, which was distal to the target location. In the future, the effect of the gradient of profile on the plan quality should be investigated when immediate dose falloff was included as the part of optimization, for example, shell constraints.…”
Section: Discussionmentioning
confidence: 99%